Factors Associated With Neural Tube Defects Among Newborns Delivered at Debre Berhan Specialized Hospital, North Eastern Ethiopia, 2021. Case-Control Study - Mulu, Getaneh Baye; Atinafu, Bantalem Tilaye; Tarekegn, Fetene Nigussie; Adane, Tigist Demssew; Tadese, Mesfin; Wubetu, Abate Dargie; Kebede, Worku Misganaw (Frontiers in Pediatrics, 2022)
Background: Neural tube defects are severe congenital malformations secondary to an abnormal closure of the neural tube between three and fourth weeks of gestational ages. Neural tube defects affect birth outcomes worldwide, with an occurrence of 18.6 per10,000 live births. In addition, neural tube defects are associated with considerable mortality, morbidity, disability, and socio-economical cost. Objective: To identify factors associated with neural tube defects among newborns delivered at Debre Berhan comprehensive specialized hospital, 2021. Methods: Facility-based case-control study design was conducted among 381(127 cases and 254 controls) newborns delivered from June 2019 to June 2021 at Debre Berhan Specialized hospital. Consecutive and systematic random sampling techniques were used to select cases and controls, respectively. Data were collected using semi-structured checklists. Finally, data were entered using Epidata version 4.2.1 and analyzed using SPSS version 25. In the bivariable logistic regression model, factors with a P-value less than 0.20 were entered into multivariable logistic regressions. Statistical significance was declared at a p-value less than 0.05. Result: In this study, 381 newborns (127 cases and 254 controls) participated with a response rate of 100%. In the logistic regression model, mothers who took medication during pregnancy [AOR 1.83(95% CI 1.08-3.08)], mothers who didn't take a balanced diet during pregnancy [AOR 13.46(95% CI 7.83- 23.13)], and mothers who didn't take folic acid before and during the first trimester of pregnancy [AOR 1.71(95% CI 1.01- 2.94)] were significantly associated with neural tube defect. Conclusion and recommendation: mothers who took medication during pregnancy, mothers who didn't take balanced diets during pregnancy, and mothers who didn't take folic acid during the pregnancy were the significant factors of neural tube defects. Health care professionals should focus on maternal safe drug prescription, maternal folate intake, and a balanced diet before and during pregnancy. Keywords: Associated factors, Neural tube defect, Newborn, Ethiopia.